Theory of origin of67zn and19f* quadrupole interactions in znf2 - Klauß, Hans Henning; Sahoo, Narayan; Kelires, Pantelis C. (My University, 1990)
The Hartree-Fock Cluster procedure for study of electronic structure has been aPPlied to investigate the nuclear quadrupole interactions of the 57Zn and 19F* nuclei in solid ZnF 2. Two different clusters, namely (ZnF6)4- and (Zn3F)5+, surrounded by a large number of lattice ions to introduce the Coulomb potential due to the rest of the solid, were used to calculate the electric field gradient parameters at the 67Zn and 19F* sites respectively. The results will be compared with that from experiment and the purely ionic model.
Keywords: Electronics; Electric fields; Ions